IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT (TQM) TOWARDS QUALITY CULTURE AT PT. COCA COLA INDONESIA - Pamungkur, Pamungkur .; Sunarmie, Sunarmie . (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
Total Quality Management (TQM) is a new paradigm for running a business that aims to maximize an organization's competitiveness through a focus on customer satisfaction, the involvement of all employees, and continuous improvement. The research objectives are: (a) To determine the extent to which the variables in the implementation of Total Quality Management which include focus on consumers, continuous improvement, management commitment, training, employee empowerment, performance comparison, and the use of statistical tools simultaneously on quality culture. (b) To ascertain the degree to which each variable in the implementation of Total Quality Management, namely customer focus, continuous improvement, management commitment, training, employee empowerment, performance comparison, and the use of statistical tools that partially affects quality culture. (c) To identify which variable in the implementation of Total Quality Management has the most dominant influence on quality culture. The method used in this research is an explanatory research with a quantitative approach on the effect of Total Quality Management Implementation on quality culture, as it aims to explain the relationship between variables through hypothesis testing, while the data used are generally numerical and are analyzed through statistical tests. The results of the study indicate that there is a significant influence between the variables in the implementation of Total Quality Management which include customer focus, continuous improvement, management commitment, training, employee empowerment, performance comparison, and the use of statistical tools simultaneously on quality culture.